The Influence of Knowledge Management on The Culture of Knowledge Sharing in The Ministry of Religion in Binjai City - Ujiani, Kartika; Sugiarto, Abdi (PT. Multidisciplinary Press Indonesia, 2024)
The aim of this research is to determine and analyze the influence of knowledge management on the culture of sharing in the Ministry of Religion of Binjai City. This research was conducted using a causal associative quantitative approach. The sample used was all employees with a total of 105 people taken using proportional sampling. The research results show that knowledge management has a positive and significant effect on sharing culture. This is shown by the T-count value of T-count of 19.564 > t table 1.65978, with a significance value of 0.000 < 0.05. The regression coefficient shows that if knowledge management is increased by 1 unit, then sharing culture will increase by 0.644 units assuming other variables remain constant. Apart from that, the results of the determination test show an Adjusted R Square value of 0.786 or 78.60%, which indicates that knowledge management has a high influence on sharing culture, while the remaining 21.40% is influenced by other factors that have not been studied. Thus, partially, knowledge management has a positive and significant effect on the culture of sharing in the Ministry of Religion of Binjai City. It identifies that improvements in knowledge management can contribute to an enhanced sharing culture.